Development of educational game-based learning media assisted by quizwhizzer to improve students' legal literacy - Atika Susanti; Ady Darmansyah (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2024)
This research aimed to develop and assess the suitability of an educational gaming media assisted by Quizwhizzer as an endeavor to enhance elementary school students' legal literacy. Employing the Research and Development (R&D) methodology within the ADDIE model (analysis, design, development, implementation, and evaluation), this study evaluated the media's suitability across three dimensions: content, language, and presentation. The findings revealed that content, language, and presentation were all validated with high scores content received an average Aiken’s V score of 0.89 (Highly Valid) with 93% agreement among validators, while language and presentation received scores of 1 (Highly Valid) with similar agreement percentages. These results collectively endorse the product's suitability for educational use. This educational gaming media was specifically evaluated for its potential to enhance second-grade students' understanding of Pancasila education, focusing on regulations to improve their legal literacy.